Comparison of Modulation Schemes for 10.7 Gb/s Transmission Over Large-Core 1 mm PMMA Polymer Optical Fiber - Loquai, Sven; Kruglov, Roman; Schmauß, Bernhard; Bunge, C. -A.; Winkler, Florian; Ziemann, Olaf; Hartl, Engelbert; Kupfer, Theodor (Journal of Lightwave Technology, 2013)
The authors give an overview of experimental results on 10.7 Gb/s over large-core 1 mm polymethyl-methacrylate (PMMA) polymer optical fiber (POF). The comparison starts with simple non-return-to-zero (NRZ) transmission without equalization. Next, measurement results with feed-forward-, decision-feedback equalization (FFE, DFE) and maximum likelihood sequence estimation (MLSE) are presented. Finally, experimental results with more advanced modulation schemes like pulse amplitude modulation (PAM) and discrete multitone (DMT) modulation are investigated. The experiments were carried out with a Vertical-Cavity Surface-Emitting Laser (VCSEL) at 0 dBm to comply with consumer eye-safety regulation or with a 10 mW laser diode (LD) that could be used in active optical cables. © 1983-2012 IEE
UnivIS-Import:2015-03-09:Pub.2013.tech.IE.LEH.compar
Keywords: Discrete multitone modulation; feed-forward and decision-feedback equalization; maximum likelihood sequence estimation; non-return-to-zero modulation; optical communication; polymer optical fiber; pulse amplitude modulation